"Piotruś Pan w Ogrodach Kensingtońskich" Jamesa Matthew Barriego - Wieczorkiewicz, Aleksandra (My University, 2016)
„All children, except one, grow up”. Among all the authors of global classic literature for children James Matthew Barrie is definitely an outstanding writer, known as the creator of the story about Peter Pan – the boy who would not grow up and who lives on the fantastical island of Neverland. However, the eternal boy not always lived on Never Never Land – although he is (and forever will be) „young”, he is not devoid of the past: his story begins in Kensington Gardens. The present MA thesis is divided into three parts. The opening part is an interpretative essay, in the first instance devoted to James Matthew Barrie himself (who’s biography – unknown in Poland – is essential to understand his work). Subsequently the essay considers textual and generic flexibility of Peter Pan and presents a comprehensive interpretation of Peter Pan in Kensington Gardens (1906) – Barrie’s very first work dedicated to the boy who would not grow up, which somehow forms the origin and prefiguration of famous Peter Pan and Wendy (1911); finally, it offers an exploration of various mythological, cultural and literary motives from which the figure of Peter Pan originates. The second section of the present MA thesis is a piece of literary translation criticism; it focuses on the two existing Polish translations of Peter Pan in Kensington Gardens: Przygody Piotrusia Pana (1913) by Zofia Rogoszówna and Piotruś Pan w Ogrodach Kensingtońskich (1991) by Maciej Słomczyński. This part consists of a comparative analysis of translations mentioned above; the main challenges that Barrie’s works pose to the translator are highlighted here and translation strategies adopted by Rogoszówna and Słomczyński are critically compared. The third part – central and the most extensive – presents the new translation of Peter Pan in Kensington Gardens, prepared by the author of the present MA thesis in the 110th anniversary of the publication of the original text. The translation is accompanied by Arthur Rackham’s Edwardian illustrations which perfectly capture Barrie’s elusive and whimsical genius, and by the brief afterward written by the youngest translator of Peter Pan in Kensington Gardens.
Keywords: James Matthew Barrie; books for children in translation; children’s classic literature; literary translation; Peter Pan in Kensington Gardens